INDUSTRIAL DEVELOPMENT IN THE SOUTHERN REGIONS OF UZBEKISTAN: HISTORICAL EXPERIENCE AND RESULTS (1925-1991) - Mamatqulov B. Sh. (TARIXIY TADQIQOTLAR, 2025)
This scientific article examines the historical experience and results of industrial development in the southern regions of Uzbekistan during the period from 1925 to 1991. The article analyzes the impact of industry on economic development, the formation of key industrial sectors, the economic and social conditions of the regions, and the significant changes in their development. Special attention is given to the factors of industrial growth, including planning, technological advancements, and the use of labor resources, as well as the successes and shortcomings of this process.